CUR LC - Szelagowski, Pablo E. M. (2003)
El autor describe las motivaciones para la temática de este número de la revista.
Keywords: LE CORBUSIER; PURINI, FRANCO; ANSALAS, JULIETA; LILI, PABLO; ARGENTINA; BUENOS AIRES (PROV); LA PLATA; VIVIENDAS UNIFAMILIARES; VIVIENDAS SUBURBANAS; MOVIMIENTO MODERNO